Deleterious BRCA1/2 mutations in an urban population of Black women - Lynce, Filipa (Breast Cancer Res Treat, 2015)
Information on the prevalence of deleterious BRCA1 and BRCA2 (BRCA1/2) mutations in clinic-based populations of Black women is limited. In order to address this gap, we performed a retrospective study to determine the prevalence of deleterious BRCA1/2 mutations, predictors of having a mutation, and acceptance of risk-reducing surgeries in Black women. In an urban unselected clinic-based population, we evaluated 211 self-identified Black women who underwent genetic counseling for hereditary breast–ovarian cancer syndrome. BRCA1/2 mutations were identified in 13.4 % of the participants who received genetic testing. Younger age at diagnosis, higher BRCA-PRO score, significant family history, and diagnosis of triple-negative breast cancer were associated with identification of a BRCA1/2 mutation. Of the affected patients found to have a deleterious mutation, almost half underwent prophylactic measures. In our study population, 1 in 7 Black women who underwent genetic testing harbored a deleterious BRCA1/2 mutation independent of age at diagnosis or family history.